2010
DOI: 10.3109/01612840903497594
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Osteoporosis in an Inpatient Geriatric Psychiatric Setting: A Pilot Study

Abstract: Osteoporosis is a major public health issue. We examined geriatric psychiatric inpatients' awareness of having osteopenia and/or osteoporosis. The much lower proportion of our patients reporting a history of osteoporosis suggests that it might be under-diagnosed in this psychiatric population. A high proportion of our sample were treated with psychotropics that may decrease bone mineral density, however, most were not receiving any treatment for osteoporosis and fewer than expected were aware of a history of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Both Stubbs et al [17] and Blair et al [18] studied osteoporosis in inpatient psychogeriatric patients. Osteoporosis has been termed the 'silent disease' as it can remain asymptomatic in the absence of fractures.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…Both Stubbs et al [17] and Blair et al [18] studied osteoporosis in inpatient psychogeriatric patients. Osteoporosis has been termed the 'silent disease' as it can remain asymptomatic in the absence of fractures.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…Other studies have shown that patients with depression are more likely to develop coronary artery disease [10], to have a stroke [11], or a heart attack [12] and the relationship between depression and pain has been documented, see [13] for a review. There is less research examining the link between depression and physical illness specifically in elderly populations but a relationship has been found between depression and cardiovascular and cerebrovascular disease [14], osteoporosis and psychiatric illness [15,16], and depression and diabetes [17]. A cross sectional study [18] found that both physical comorbidities and functional limitations increased the likelihood of depressive illness in older persons and a meta-analysis found that chronic illness was a risk factor for depression in this age group [19].…”
Section: Introductionmentioning
confidence: 99%